PP.09.20: THE RELATIONSHIP BETWEEN DAY AND NIGHT URINARY CORTISOL METABOLITES AND VASCULAR RESPONSE IN PARTICIPANTS WITH OR AT RISK OF TYPE 2 DIABETES. (June 2015) - Mills, C.E.; Crickmore, H.; Iqbal, F.; Risser, A.; Bobeica, D.; Ghataore, L.; Govoni, V.; Scott, D.; Casagrande, M.; Webb, A.J.; Taylor, N.F.; Cruickshank, J.K.
Abstract : Objective: To assess if 24 h urinary steroid metabolite profiles are related to vascular parameters such as arterial stiffness and blood pressure (BP) Design and method: 43 eligible participants, 25–81 years, with eGFR > 45 mL/min and no serious illness. Urine was collected over 24 h (12 h day and night samples). Peripheral BP, central pulse wave velocity (aPWV) (by Arteriograph) and cardio ankle vascular index (CAVI) (by VaSera) measures were performed on the collection day. Steroids were extracted from urine aliquots and conjugates hydrolysed by Helix pomatia digestive juice. Free steroids were re-extracted and methyl oxime-trimethylsilyl ether derivatives prepared for GC-MS analysis. Pearson correlation and multiple regression analysis were performed. Results: The urinary steroid metabolites detailed in the figure (figure on the following page) were quantified. Systolic BP and aPWV correlated positively with the ratio of cortisol to cortisone metabolites [aTHF, THF, αcol and βcol: THE, αcone and βcone, (colmets: conemets)]; r = 0.32, 0.37 respectively, p < 0.05 for day samples and r = 0.33, 0.34 respectively, p < 0.05 for night samples. Both BP and aPWV also correlated negatively in the day samples with the ratio αcol, βcol, αcone and βcone: aTHF, THF and THE (20OH: 20oxo); r = -0.33, -0.32 respectively, p < 0.05. Night samples only showed this correlation with diastolic BP r = 0.31, p < 0.05. No correlations were seen with CAVI. Regression analysis with these metabolite ratios (including age and body mass index) did not show they were associated with BP or CAVI (including BP). While aPWV was borderline associated with colmets: conemets, p = 0.077, 20OH: 20oxo was significantly associated (p = 0.026). BP and BMI remained independent predictors. Conclusions: 24 h urinary 20OH:20oxo ratio was independently related to aPWV in those with or at risk of T2D and colmets:conemets had borderline associations with aPWV. There were no associations with the urinary steroids and BP. Figure. No caption available.